Evaluasi Efek Samping Penggunaan Nsaid Pada Pasien Osteoartritis Di Instalasi Rawat Jalan RSUD R.A. Kartini Jepara - Nuzulatul Wahyu Mustika Ningrum; Ria Etikasari; Ulviani Yulia Husna (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Osteoarthritis (OA) is a common degenerative disease in the elderly and a leading cause of disability. Excessive joint pain results in limited daily activities. In pharmacological therapy, Nonsteroidal Anti-inflammatory Drugs (NSAIDs) are the main choice for OA treatment. Appropriate use of NSAIDs in OA patients is essential to achieve optimal therapeutic outcomes. This study aimed to analyze and evaluate adverse effects of NSAID use in OA patients at the Outpatient Installation of RSUD R.A. Kartini Jepara. The research was conducted using a descriptive observational method with a retrospective design based on secondary data from medical records. Samples were determined through purposive sampling with inclusion criteria: OA patients aged 45–75 years who had at least three visits during January–December 2024. Exclusion criteria were incomplete or unreadable medical records. Data were analyzed descriptively to present patient characteristics, NSAID usage profiles, and adverse effects. The results showed that OA patients were predominantly female (72.9%), aged 65–75 years (46.9%), and had BMI >27 (53.1%). Most patients had disease duration >12 months (38.4%) and received NSAID therapy for more than 3 weeks (70.8%). Hypertension was the most common comorbidity (50%), while the most frequently used concomitant medications were gastrointestinal drugs (23.98%) and antihypertensives (23.17%). Meloxicam was the most frequently prescribed NSAID (51%). The most common adverse effects were gastrointestinal disorders, including dyspepsia (56.10%) and vertigo (17.07%).